Penulisan Narasi Ekspositoris Dalam Produksi Film Dokumenter “Apocalyptic Tides” - Dimas Althalaric Mohammad Sultan; Yabes Yedija Wesley; Toto Sugito; Aat Ruchiat Nugraha (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
The documentary film “Apocalyptic Tides” is an audiovisual work that explores the phenomenon of ocean-borne waste in coastal areas. The writer acts as the scriptwriter, focusing on the development of an expository narrative as the foundational structure for both the storyline and the creative aspects of the film. The narrative employs a three-act structure with a suggestive storytelling approach, utilizing various rhetorical devices to evoke a strong emotional response from the audience. An expository narrative method is used to convey factual information clearly and thoroughly, structured through an introduction of the issue via observational visuals and voice-over, a depiction of the ecological conflict caused by ocean-borne waste, and a resolution that reveals deeper insights into the underlying problem. The result demonstrates that the use of an expository narrative can effectively build public awareness of the ecological crisis caused by waste accumulation, particularly during the monsoon season. This film serves not only as an informative medium but also as a communicative tool that evokes empathy toward coastal ecosystem degradation.